For the expression 11 / 12 + ( - 1 / 11 ), we get the result as 109 / 11.
We are given the expression:
11 / 12 + ( - 1 / 11 )
We need to find the value of the expression.
We will first open the brackets.
We know that ( + ) ( - ) = ( - )
So, we get that:
= 11 / 12 - 1 / 11
Now we will take the LCM.
LCM of 11 and 12 = 132
So, we get that:
= (121 - 12) / 11
= 109 / 11
Therefore, for the expression 11 / 12 + ( - 1 / 11 ), we get the result as 109 / 11.
Learn more about expression here:
https://brainly.com/question/723406
#SPJ9